2003
DOI: 10.1016/s0167-0115(02)00253-7
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II mediates catecholamine and neuropeptide Y secretion in human adrenal chromaffin cells through the AT1 receptor

Abstract: The aim of the present work was to study the effect of angiotensin II (Ang II) on catecholamines and neuropeptide Y (NPY) release in primary cultures of human adrenal chromaffin cells. Ang II stimulates norepinephrine (NE), epinephrine (EP) and NPY release from perifused chromaffin cells by 3-, 2-and 12-fold, respectively. The NPY release is more sustained than that of catecholamines. We found that the receptor-AT 2 agonist, T 2 -(Ang II 4 -8) 2 has no effect on NE, EP and NPY release from chromaffin cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Other neuronal elements including sensory and parasympathetic neurons, expressing opioid peptides, vasoactive intestinal polypeptide (VIP) or substance P (SP), as well as Type I and II intramedullary ganglionic cells, play a role in the physiological regulation of this gland (Mravec 2005). Additional factors such as angiotensin II, histamine, glucocorticoids and gonadal steroids act as endocrine or paracrine/autocrine modulators of adrenomedullary activity (Cavadas et al 2003;Marley 2003;Schinner and Bornstein 2005). Signalling from the activated immune system is little explored, despite being a potentially important non-neural adrenomedullary regulator.…”
Section: Introductionmentioning
confidence: 99%
“…Other neuronal elements including sensory and parasympathetic neurons, expressing opioid peptides, vasoactive intestinal polypeptide (VIP) or substance P (SP), as well as Type I and II intramedullary ganglionic cells, play a role in the physiological regulation of this gland (Mravec 2005). Additional factors such as angiotensin II, histamine, glucocorticoids and gonadal steroids act as endocrine or paracrine/autocrine modulators of adrenomedullary activity (Cavadas et al 2003;Marley 2003;Schinner and Bornstein 2005). Signalling from the activated immune system is little explored, despite being a potentially important non-neural adrenomedullary regulator.…”
Section: Introductionmentioning
confidence: 99%
“…though the AT1 receptor has been implicated in mediating catecholamine secretion from mammalian chromaffin cells (9), the specific ANG II receptor subtype has not yet been identified in any fish species, although there is evidence that the piscine receptor is AT1-like (15,57). Once the specific chromaffin cell ANG II receptor is identified in rainbow trout, future studies should be directed at quantifying their expression levels in response to dietary salt loading.…”
Section: Catecholamine Secretion In Hypertensive Fishmentioning
confidence: 99%
“…Catecholamine secretion in human chromaffin cells is regulated by NPY, presumably acting via the putative y3 receptor (Cavadas et al 2001), though factors such as angiotensin II (Cavadas et al 2003) or interleukin-1b (Rosmaninho-Salgado et al 2009) have also been found to regulate the release of catecholamines and NPY.…”
Section: Chromaffin Vesiclesmentioning
confidence: 99%